The Implementation of Digital Twin Technology in Construction Projects in Malaysia - Jamri, Iezza Nadia; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2026)
The Malaysian construction industry continues to face persistent challenges such as project delays, cost overruns, inefficient asset utilization, and reliance on conventional maintenance practices due to limited real-time data integration To address these challenges, the adoption of advanced technologies has emerged as a transformative approach in reshaping construction project management by enhancing efficiency, reducing risks, and improving overall project performance.Digital Twin technology refers to a digital representation of physical assets that integrates real-time data to enable monitoring, simulation, and informed decision-making throughout the asset lifecycle. This study aims to explore the implementation of Digital Twin technology in Malaysia’s construction industry, focusing on its potential benefits and adoption strategies. A qualitative research approach was employed, involving semi-structured interviews with industry experts, and the collected data were analyzed using thematic analysis to identify key patterns and industry trends. The findings reveal that although Digital Twin technology offers significant advantages, including predictive maintenance, real-time monitoring, and lifecycle optimization, its implementation is constrained by high initial costs, limited technical expertise, and low awareness among industry stakeholders. In conclusion, this study highlights that while Digital Twin technology possesses transformative potential for Malaysia’s construction industry, its successful adoption requires strategic planning, policy support, and enhanced industry readiness.